Surgical treatment of traumatic fractures of the thoracic and lumbar spine: A systematic review - Timon F.G. Vercoulen; Menco J.S. Niemeyer; Felix Peuker; Jorrit-Jan Verlaan; F. Cumhur Oner; Said Sadiqi (Brain and Spine)
Introduction: The treatment of traumatic thoracic and lumbar spine fractures remains controversial. To date no consensus exists on the correct choice of surgical approach and technique. Research question: to provide a comprehensive up-to-date overview of the available different surgical methods and their quantified outcomes. Methods: PubMed and EMBASE were searched between 2001 and 2020 using the term ‘spinal fractures’. Inclusion criteria were: adults, ≥10 cases, ≥12 months follow-up, thoracic or lumbar fractures, and surgery <3 weeks of trauma. Studies were categorized per surgical technique: Posterior open (PO), posterior percutaneous (PP), stand-alone vertebral body augmentation (SA), anterior scopic (AS), anterior open (AO), posterior percutaneous and anterior open (PPAO), posterior percutaneous and anterior scopic (PPAS), posterior open and anterior open (POAO) and posterior open and anterior scopic (POAS). The PO group was used as a reference group. Results: After duplicate removal 6042 articles were identified. A total of 102 articles were Included, in which 137 separate surgical technique cohorts were described: PO (n = 75), PP, (n = 39), SA (n = 12), AO (n = 5), PPAO (n = 1), PPAS (n = 1), POAO (n = 2) and POAS (n = 2). Discussion and conclusion: For type A3/A4 burst fractures, without severe neurological deficit, posterior percutaneous (PP) technique seems the safest and most feasible option in the past two decades. If needed, PP can be combined with anterior augmentation to prevent secondary kyphosis. Furthermore, posterior open (PO) technique is feasible in almost all types of fractures. Also, this technique can provide for an additional posterior decompression or fusion. Overall, no neurologic deterioration was reported following surgical intervention.